Competence Of Mothers and Cadres in Early Detection Of Stunting in 3 Provinces in Indonesia - Muhasidah Muhasidah; Hartati Hartati; Baharuddin Baharuddin; Azizah Saleh (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Stunting can affect a child's growth and development, leading to low human resource quality, thus posing a risk to work productivity. The stunting rate has increased significantly over the past 10 years, particularly in Eastern Indonesia, requiring serious attention from various professions, particularly the government, in collaboration with health workers. Research Objectives: 1) To identify the understanding, attitudes, and skills of mothers and health workers regarding the recognition, early detection, and risk factors of stunting, 2) increasing the knowledge of mothers and health cadres about early detection of stunting from the womb to the first 1000 days of life, and 3) To design an effective and practical guidebook that mothers and health workers can use to identify, early detection, and risk factors for stunting in the first 1,000 lives.  Methods: This quantitative research study used a descriptive analytical design using a "One Group Pre-Post Test Design" and a pre-experimental method. The sample size was 210 mothers and health workers using a purposive sampling technique in the cities of Makassar, Mataram, and Soe, NTT.  The results of the study in Makassar City and Soe City (NTT) showed that the level of knowledge of mothers about early detection of stunting was mostly lacking, namely 136 (93.8%). The level of knowledge of cadres about early detection of stunting was mostly high, namely 13 people (86.7%). Most were lacking, namely 113 (93.42%). While the skills of cadres about early detection of stunting were mostly good, namely 55 people (61.8%). The mother's attitude towards early detection of stunting was mostly lacking, namely 106 (99.1%). Meanwhile, the cadre's attitude towards early detection of stunting was mostly good, namely 62 people (60.2%). The statistical test results obtained p = 0.000, so it can be concluded that there is a difference in the proportion of the level of knowledge, skills and attitudes of mothers and health cadres with the ability to recognize early detection and risk factors stunting. Conclusion: Knowledge, skills and attitudes of mothers and health cadres are very lacking regarding the introduction, early detection and risk factors for stunting, and there is a significant relationship between the level of knowledge, skills and attitudes of mothers and health cadres, with the introduction of early detection and risk factors for stunting.